China's claim to a new world order - Nadine Godehardt; Maximilian Mayer (Stiftung Wissenschaft und Politik (SWP), 2025)
This year's Shanghai Cooperation Organization (SCO) summit in Tianjin marked the largest gathering in the organisation's history, drawing more than 20 heads of state and 10 representatives of international organisations. At the SCO+ session, China's Head of State and Party Leader Xi Jinping delivered a keynote address, prominently unveiling the Global Governance Initiative (GGI). For Beijing, development, security, civilisation, and governance constitute the four pillars of building a "community with a shared future for mankind", in essence, a new world order. Amid today's ongoing upheavals, it is imperative for Germany and Europe to recognize China as a global strategic challenge.
Keywords: 320; China; Russia; Xi Jinping; Shanghai Cooperation Organization (SCO); Global Governance Initiative (GGI); new world order; Germany; Europe; Global South; critical raw materials